Cytotoxic Activity, Apoptosis Induction and Cell Cycle Arrest in Human Breast Cancer (MCF7) Cells by a Novel Fluorinated Tetrahydro-[1, 2, 4]Triazolo[3, 4-a]Isoquinolin Chalcones. (2nd January 2023) - Mohamed, Magda F.; Ibrahim, Nada S.; Ibrahim, Sherif Abdelaziz; El-Manawaty, May A.; El-Hallouty, Salwa M.; Hassaneen, Hamdi M.; Abdelhamid, Ismail A.
Abstract: A series of fluorinated chalcones (3a-f ) was synthesized and confirmed by several spectral tools. The cytotoxic effect of this series was tested against a panel of different cancer cell lines (MCF7, A549, HCT116, and PC3). MTT assay revealed that chalcone 3f has the potent cytotoxic activity against all tested cancer cell lines except A549 cells. Chalcone 3f showed the least cytotoxic activity against the normal epithelial cell line RPE-1 and the lowest IC50 at 10.96 µM relative to the IC50 of doxorubicin at 12.8 µM against the human breast cancer cell line MCF7. Molecular docking studies showed a good interaction of chalcone 3f with the active site of histone demethylase (PLU-1/JARID1B) and Carboxy-terminal binding protein1 (CtBP1) proteins. Mechanistically, chalcone 3f induced cell cycle arrest at G2/M phase and apoptosis assessed by flow cytometry, as well as DNA fragmentation in MCF7 cells. Chalcone 3f upregulated mRNA expression levels of the apoptotic genes BAX, p53, and Caspase-7, Caspase-8, and Caspase-9, whereas mRNA expression levels of the antiapoptotic gene Bcl2, metastasis-related gene matrix metalloproteinase 1 ( MMP1 ), and the autophagic markers ATG5 and LC3B were downregulated as quantified by qPCR. This study shows a cytotoxic effect of chalcone 3f against cancer cells and emerges as a promising therapeutic drug against breast cancer. Graphical Abstract: UF0001